Correlation of Knowledge, Attitudes and Behaviors of a Mother about Breastfeeding with Nutritional Status of Children Aged 6-23 of Sukmajaya Health Center, Depok City - Resti Ayu Apriyanti; Firlia Ayu Arini; Ikha Deviyanti Puspita (Universitas Islam Negeri Walisongo Semarang, 2018)
The aim of this study was to analyze the correlation of knowledge, attitudes and behaviors of a mother about breastfeeding with the nutritional status of children aged 6-23 months by using cross sectional design. The target population were all mothers with children aged 6-23 months. The samples were 179 respondents using purposive sampling techniques. Retrieval of data was done using questionnaires and structured interviews. Statistical calculation performed using univariate and bivariate analysis with chi-square test. The result showed that there was no correlation between maternal knowledge with BB/U (p=0,056), though there was a correlation between maternal attitudes with BB/U (p=0,000) and maternal behaviors with BB/U (p=0,000). It is concluded that there was significant correlation between attitudes and behavior of mothers with nutritional status of children aged 6-23 months. It is suggested to nutrition counselor to add more education related to exclusive breastfeeding.